The History and Development of the Gereja Batak Karo Protestan (GBKP), 1990-2010 - Marcopan Bastian; Budi Agustono; Fikarwin Zuska (Warisan: Journal of History and Cultural Heritage, 2024)
This article discusses the Gereja Batak Karo Protestan (GBKP) museum between 1990 and 2010 using historical research methods consisting of heuristics, verification, interpretation, and historiography. The research results show that the existence of GBKP in Karo is closely linked to the evangelists or Zending who arrived in the area in the late 19th century to carry out the Christianization process. Although the Christianization efforts seemed slow, they were ultimately successful as the majority of the Karo people embraced Christianity and began building churches as places of worship into the 21st century. The uneven distribution of the Karo population across regions led to some churches becoming uninhabited, prompting their conversion into a museum in 1990. The museum aims to introduce and preserve the ancestral heritage of the Karo people. Despite low visitor interest, efforts to preserve the museum continue as a way to maintain the memory and identity of the Karo people through various challenges.